(untitled) (Computer systems and information technologies, 2025)
The intensification of production at petrochemical, construction, industrial, and energy companies and the aging of equipment at major technological and energy facilities lead to increased emissions of toxic and dusty substances into the air, soil, and water. As a result of the ecosystem cycle, these chemical compounds enter the soil and water, causing pollution. The main task of environmental expertise is to determine the degree of risk and safety of industrial activity, organize a program of expert assessment of industrial production facilities, establish compliance of facilities with the requirements of environmental legislation, examine the quality of natural resources, form a balance of quality criteria for the environmental safety of facilities and the environment, assess the negative impact of industrial and municipal structures on the environment, and expertly evaluate programs for the introduction of new technology. Air monitoring is necessary to detect the effects of pollutants and their impact on: corrosion of structures, erosion of land resources, impact on human health, impact on flora and the environment, water pollution, and food contamination. The article highlights the basic concepts for building information and measuring systems (laser concentrometer and opto-galvanic sensors) for rapid analysis of environmental pollution such as air, water, and soil in emergency and extreme situations. The air and water pollution was detected around energy facilities and various industrial production facilities that are at risk of military attack. The article describes the development and construction of a laser information and measurement system for measuring dust in the atmosphere and presents the results of a study of the chemical pollution of water wells in various industries.